Systemic Review of Sustainable Urbanization: Challenges and Solutions for Effective Urban Planning in Pakistan - Begum, Azeema; Abro, Moied Uddin (Unisia, 2024)
Sustainable urbanization is a crucial topic in the fight against environmental issues, fast urbanization, rising energy, transportation needs, and reduced quality of life. Rapid urbanization, population growth, a lack of administrative response to issues, and rising energy and transportation costs have made ensuring sustainable urban development a major concern in emerging countries. This research aims to identify challenges Pakistan is currently facing regarding sustainable urbanization and effective urban planning. This study adopted a systematic literature review to find the most relevant 27 articles using a systematic process and analyzed them using thematic analysis. Based on findings, it has been found that the pace of urbanization without conserving sustainability has raised serious concerns about urban planning. Several issues and challenges, such as inadequate infrastructure, political resistance, uncoordinated urban growth, lack of sustainable infrastructure, and difficulty in adapting urban policies to sustainability requirements, are major concerns impacting efforts related to sustainable urban planning in Pakistan. Addressing these concerns is essential to maximizing productivity and guaranteeing the long-term viability of sustainable urban expansion. As a result, national policymakers must emphasize sustainable urban planning to achieve long-term economic growth.